Peripheral endothelial dysfunction is a novel risk factor for systolic dysfunction and heart failure progression. (October 2020) - Taher, Riad; Sara, Jaskanwal D.; Toya, Takumi; Borlaug, Barry A.; Lerman, Lilach O.; Lerman, Amir
Highlights: Peripheral endothelial dysfunction (PED) predicts adverse outcomes in patients with stage B HF. PED was independently associated with stage B HF, even after adjusting for co-variables. PED was strongly associated with progression from stage B to overt stage C HF. Detecting PED may stratify the risk of HF progression. Abstract: Background: ACC/AHA guidelines recognize the progressive nature of heart failure (HF). Patients with risk factors (Stage A) are at risk for developing asymptomatic cardiac dysfunction (Stage B), which may then lead to symptomatic HF (Stage C). As such, therapies targeting abnormalities in stages A and B may protect against development of symptomatic HF. peripheral endothelial dysfunction (PED) is an independent predictor of adverse outcomes in patients with stage C HF. The aim of the current study was to evaluate whether PED might be associated with Stage B HF, where therapeutic interventions to prevent progression might be more efficacious. Methods: We performed a retrospective cross-sectional analysis of patients who were referred for routine cardiovascular evaluation that included an assessment of peripheral endothelial function with reactive hyperemia-peripheral arterial tonometry. Individuals in this study underwent routine clinically indicated echocardiography within 2 months of testing for PED. Patients with clinical HF were excluded. Results: The study included 355 patients (mean age 51.5 ± 14.6 years, 231 (65.1%) female). There was a significant association between PED and Stage B HF (Odds Ratio (OR) 6.38; P < 0.0001) that persisted after stratifying by sex. In multivariate analyses PED was significantly associated with Stage B HF (OR 5.33; P = 0.0038), and was also associated with progression to overt stage C HF (OR 4.63; P = 0.033). Conclusion: Peripheral endothelial dysfunction is risk factor for Stage B HF, even in low risk individuals. Further study is warranted to better understand the mechanistic basis of PED in HF to reduce the risk of symptomatic progression.